2022
DOI: 10.3389/fpubh.2022.1042218
|View full text |Cite
|
Sign up to set email alerts
|

Prediction of suicidal ideation among Chinese college students based on radial basis function neural network

Abstract: BackgroundSuicide is one of the leading causes of death for college students. The predictors of suicidal ideation among college students are inconsistent and few studies have systematically investigated psychological symptoms of college students to predict suicide. Therefore, this study aims to develop a suicidal ideation prediction model and explore important predictors of suicidal ideation among college students in China.MethodsWe recruited 1,500 college students of Sichuan University and followed up for 4 y… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
6
0
1

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 10 publications
(7 citation statements)
references
References 94 publications
0
6
0
1
Order By: Relevance
“…Noteworthily, suicidal ideation at baseline could be leveraged by the machine to predict suicidal ideation after six months, but it did not yield a strictly statistically significant role. To our knowledge, there have been several studies implementing machine learning models leveraging previous suicidal ideation to predict future suicidal ideation (Benjet et al, 2022;Liao et al, 2022;Malone et al, 2021), although timeframes from baseline to follow-up did not coincide with our six-month timeframe. Substantially, previous suicidal ideation is an important is the author/funder, who has granted medRxiv a license to display the preprint in (which was not certified by peer review) preprint…”
Section: Discussionmentioning
confidence: 93%
See 1 more Smart Citation
“…Noteworthily, suicidal ideation at baseline could be leveraged by the machine to predict suicidal ideation after six months, but it did not yield a strictly statistically significant role. To our knowledge, there have been several studies implementing machine learning models leveraging previous suicidal ideation to predict future suicidal ideation (Benjet et al, 2022;Liao et al, 2022;Malone et al, 2021), although timeframes from baseline to follow-up did not coincide with our six-month timeframe. Substantially, previous suicidal ideation is an important is the author/funder, who has granted medRxiv a license to display the preprint in (which was not certified by peer review) preprint…”
Section: Discussionmentioning
confidence: 93%
“…Noteworthily, suicidal ideation at baseline could be leveraged by the machine to predict suicidal ideation after six months, but it did not yield a strictly statistically significant role. To our knowledge, there have been several studies implementing machine learning models leveraging previous suicidal ideation to predict future suicidal ideation (Benjet et al, 2022; Liao et al, 2022; Malone et al, 2021), although timeframes from baseline to follow-up did not coincide with our six-month timeframe. Substantially, previous suicidal ideation is an important factor, posing a greater risk of future suicidal ideation and suicidal behavior (Bafna et al, 2022), but in our analysis did not reach canonical statistical significance (although it should be taken into account that the machine learning model would lose a great proportion of its accuracy without data from previous suicidal ideation – Figure 3A).…”
Section: Discussionmentioning
confidence: 99%
“…, 2022 ; Liao et al. , 2022 ; Malone et al. , 2021 ), although time frames from baseline to follow-up did not coincide with our 6-month time frame.…”
Section: Discussionmentioning
confidence: 48%
“…Noteworthily, suicidal ideation at baseline could be leveraged by the machine to predict suicidal ideation after 6 months, but it did not yield a strictly statistically significant role. To our knowledge, there have been several studies implementing machine learning models leveraging previous suicidal ideation to predict future suicidal ideation (Benjet et al, 2022;Liao et al, 2022;Malone et al, 2021), although time frames from baseline to follow-up did not coincide with our 6-month time frame. Substantially, previous suicidal ideation is an important factor, posing a greater risk of future suicidal ideation and suicidal behaviour (Bafna et al, 2022), but in our analysis, this prediction did not reach canonical statistical significance (although it should be taken into account that the machine learning model would lose a great proportion of its accuracy without data from previous suicidal ideation -Figure 3A).…”
Section: Discussionmentioning
confidence: 96%
“…Our findings extend these observations over the non-clinical sample of individuals with less severe psychopathological symptoms. Moreover, a recent study performed in college students demonstrated that previous suicidal ideation and low subjective quality of sleep are the most robust predictors of the current suicidal ideation [ 51 ]. Other factors associated with higher risk of the current suicidal ideation in this sample included paranoid thoughts, internet addiction, poor self-rated physical health, poor self-rated overall health, emotional abuse, low average annual household income per person and heavy study pressure.…”
Section: Discussionmentioning
confidence: 99%